Pyridine Carboxamides Based on Sulfobetaines: Design, Reactivity, and Biological Activity - Eugene P. Kramarova; Sophia S. Borisevich; Edward M. Khamitov; Alexander A. Korlyukov; Pavel V. Dorovatovskii; Anastasia D. Shagina; Konstantin S. Mineev; Dmitri V. Tarasenko; Roman A. Novikov; Alexey A. Lagunin; Ivan Boldyrev; Aiarpi A. Ezdoglian; et al. (Molecules, 2022)
The synthesis of the products of the 1,3-propanesultone ring opening during its interaction with amides of pyridinecarboxylic acids has been carried out. The dependence of the yield of the reaction products on the position (ortho-, meta-, para-) of the substituent in the heteroaromatic fragment and temperature condition was revealed. In contrast to the meta- and para-substituted substrates, the reaction involving ortho-derivatives at the boiling point of methanol unexpectedly led to the formation of a salt. On the basis of spectroscopic, X-Ray, and quantum-chemical calculation data, a model of the transition-state, as well as a mechanism for this alkylation reaction of pyridine carboxamides with sultone were proposed in order to explain the higher yields obtained with the nicotinamide and its N-methyl analog compared to ortho or meta parents. Based on the analysis of ESP maps, the positions of the binding sites of reagents with a potential complexing agent in space were determined. The in silico evaluation of possible biological activity showed that the synthetized compounds revealed some promising pharmacological effects and low acute toxicity.